The Impact of Internal Control, Good Governance, and Organizational Commitment on Institutional Performance - Eliana; Ainul Ridha; Farah Ivana (Academic Bright Collaboration, 2026)
Purpose –This study investigates the impact of internal control, good governance, and organizational commitment on institutional performance at the Regional Financial Management Agency (BPKD) of Aceh Besar. It aims to understand how these factors influence public sector performance, focusing on local government financial management in Indonesia.Methods –A quantitative survey was conducted with 93 employees at BPKD Aceh Besar. Descriptive statistics and regression analysis were used to examine the relationships between the three factors and institutional performance.Findings –Internal control (3.94), good governance (3.91), and organizational commitment (3.88) were found to positively impact institutional performance (3.92). Internal control, particularly risk identification and fraud prevention, was the most influential factor. Organizational commitment, though strong, showed potential for improvement in employee comfort.Research Implications –The findings highlight the need for local government agencies to strengthen internal control systems, enhance governance practices, and foster employee commitment. Future research should explore causal relationships and consider external factors like leadership styles.Originality –This study integrates key organizational factors to assess their combined impact on public sector performance, offering valuable insights into local government management in Indonesia.